Assessment and Accountability in Higher Education: A Program's Response - Irma O'Dell (Educational Considerations, 2009)
Pressure from external stakeholders increasingly requires higher education institutions to provide concrete evidence of student learning, i.e., learning that will assist graduates to become productive, working members of society.
Keywords: Kansas State University; assessment; student; learning; methods; successful; Leadership; effective; academic; professional